Predictors of Bilateral Disease in Pediatric Differentiated Thyroid Cancer - Cherella, Christine E; Richman, Danielle M; Liu, Enju; Frates, Mary C; Modi, Biren P; Zendejas, Benjamin; Smith, Jessica R; Barletta, Justine A; Hollowell, Monica L; Wassner, Ari J (The journal of clinical endocrinology and metabolism, 2021)
Abstract Context Total thyroidectomy is recommended for children with papillary thyroid carcinoma, partly because of a high prevalence of bilateral disease. Identifying characteristics that predict bilateral disease might identify candidates for more limited surgery. Objective Investigate associations of preoperative or histopathological characteristics with bilateral disease in children with differentiated thyroid cancer. Methods Retrospective cohort study (1998-2020) at 2 academic hospitals. Patients <19 years who underwent total thyroidectomy for differentiated thyroid cancer were included. Clinical, sonographic, and histopathological characteristics were evaluated. The presence of bilateral disease on histopathology was assessed by univariable analysis and multivariable logistic regression. Results One hundred and fifteen subjects were analyzed (90% with papillary carcinoma). Median (range) age at diagnosis was 15.0 (8.1-18.9) years. Bilateral disease was present in 47/115 subjects (41%). Bilateral disease was associated with solid parenchyma, calcifications, irregular margins, and abnormal lymph nodes detected by ultrasound, Bethesda class V/VI cytology, papillary histology, tumor multifocality in the primary lobe, extrathyroidal extension, lymphovascular invasion, and nodal metastases. In multivariable analysis, only multifocality in the primary lobe was independently associated with bilateral disease (OR 7.61, 95% CI 2.44-23.8, P < .001). Among clinically node-negative subjects with papillary carcinoma who did not have tumor multifocality in the primary lobe, bilateral disease was present in 5/32 (16%). Conclusions In children with differentiated thyroid cancer, tumor multifocality in the primary lobe is associated with bilateral disease and should prompt consideration of completion thyroidectomy after initial lobectomy. Clinically node-negative children with tumors that are unifocal in the primary lobe have a low likelihood of contralateral disease.